COVID-19 and Pretentious Psychological Well-Being of Students: A Threat to Educational Sustainability - Li, Hui; Hafeez, Hira; Zaheer, Muhammad Asif (Frontiers in Psychology, 2021)
Since the outbreak of COVID-19, reaction quarantine, social distancing, and economic crises have posed a greater risk to physical and psychological health. Such derogatory mental health stigma is associated with adverse outcomes in the student population. The purpose of the current study is to provide a timely evaluation of the COVID-19 pandemic and its adverse effects on students' psychological well-being to sustain economic sustainability. A thorough review of the literature and current studies, the significant emphasis of socio-demographic indicators, interpretation of physical symptoms, home quarantine activities, and COVID-19 unique stressors were extracted. Data was collected through electronic surveys from 640 university students at local and foreign universities. The findings revealed substantial adverse effects resulting in varying levels of stress, symptoms of depression, and specific discomfort in the case. Among COVID-19 stressors, financial instability, unpredictability towards future/career, and media exposure have been described as common factors that cause poor psychological well-being and weaken economic sustainability. COVID-19, quarantine, self-isolation, and onerous interventions primarily weaken university students' mental health. The emphasis on this vulnerable category, however, is substantially absent from the literature. This research addresses the urgent need to develop possible solutions and preventive measures to promote economic sustainability by ensuring students' psychological well-being.